A 4-week study assessing the pharmacokinetics, pharmacodynamics, safety, and tolerability of the glucagon receptor antagonist PF-06291874 administered as monotherapy in subjects with type 2 diabetes mellitus. (April 2017) - Bergman, Arthur; Tan, Beesan; Somayaji, Veena R.; Calle, Roberto A.; Kazierad, David J.
Highlights: PF-06291874 was generally well tolerated and had a low risk for hypoglycemia. PF-06291874 resulted in robust reductions in plasma glucose levels in T2DM patients. PF-06291874 had minimal effects on plasma LDL-C at clinically relevant doses. Abstract: Aims: The glucagon receptor antagonist PF-06291874 has demonstrated robust glucose reductions in subjects with type 2 diabetes mellitus (T2DM) on background metformin. This study assessed the pharmacokinetics, pharmacodynamics, safety, and tolerability of PF-06291874 administered as monotherapy in subjects with T2DM. Methods: After a ≥4-week antidiabetic therapy washout period, 172 subjects were randomized to placebo or PF-06291874 15, 35, 75, or 150 mg once daily for 28 days. Mean daily glucose (MDG), fasting plasma glucose (FPG), and predefined safety endpoints were assessed at baseline and day 28. Results: Dose-dependent reductions (placebo-adjusted) from baseline in MDG ranged from 40.3 to 68.8 mg/dL and in FPG from 27.1 to 57.2 mg/dL after 28 days of dosing with PF-06291874. There were no significant changes in low-density lipoprotein cholesterol at doses ≤75 mg relative to placebo. Small, dose-dependent increases in alanine aminotransferase and aspartate aminotransferase were observed; however, the incidence of these values >3 × upper limit of normal was similar across doses. PF-06291874 exposures were consistent with previous studies and PF-06291874 was well tolerated, with minimal incidence of hypoglycemia. Conclusions: PF-06291874 as monotherapy was well tolerated and produced robust reductions in plasma glucose following 4 weeks of dosing in subjects with T2DM.